2020
DOI: 10.3390/app10228279
|View full text |Cite
|
Sign up to set email alerts
|

Sintering Behavior of a Six-Oxide Silicate Bioactive Glass for Scaffold Manufacturing

Abstract: The intrinsic brittleness of bioactive glasses (BGs) is one of the main barriers to the widespread use of three-dimensional porous BG-derived bone grafts (scaffolds) in clinical practice. Among all the available strategies for improving the mechanical properties of BG-based scaffolds, strut densification upon sintering treatments at high temperatures represents a relatively easy approach, but its implementation might lead to undesired and poorly predictable decrease in porosity, mass transport properties and b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

6
4

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 40 publications
3
11
0
Order By: Relevance
“…Porous scaffolds based on 1d glass were produced by the foam replica method according to a processing schedule that was previously applied on a broad range of glass compositions [24]. Briefly, a polyurethane (PU) sponge panel (45 ppi) was cut into 10 mm × 10 mm × 10 mm cuboids using a scalpel, and the small foam blocks were then soaked in a glass-containing suspension to carry out the replication process.…”
Section: Fabrication Of Scaffoldsmentioning
confidence: 99%
“…Porous scaffolds based on 1d glass were produced by the foam replica method according to a processing schedule that was previously applied on a broad range of glass compositions [24]. Briefly, a polyurethane (PU) sponge panel (45 ppi) was cut into 10 mm × 10 mm × 10 mm cuboids using a scalpel, and the small foam blocks were then soaked in a glass-containing suspension to carry out the replication process.…”
Section: Fabrication Of Scaffoldsmentioning
confidence: 99%
“…The higher content of Ce 4+ as was revealed by UV-Vis analysis can lead to aggregation effect and consequently to distortion of the glass matrix. The data from the literature reported that the compressive strength of bioactive glass scaffolds ranges from 0.2 to 150 MPa depending on the scaffold’s composition, microstructure, and preparation method [ 35 , 36 ]. It is known that while the compressive strength of human cortical bone ranges between 90 and 209 MPa, the strength of cancellous bone is between 1.5 and 45 MPa [ 37 ].…”
Section: Resultsmentioning
confidence: 99%
“…The structural analysis of skeletal body elements and of biomechanical systems consisting of a bone element coupled to a prosthesis, an implant or a fracture synthesis device, can be performed both numerically and experimentally [18]. There are many examples of clinical problems, which have moved from a qualitative assessment to a quantitative evaluation thanks to the respective modelling or to the application of classical experimental methods of structural analysis to the evaluation of the efficacy of procedures or surgical techniques or to the evaluation of the mechanical characteristics of the materials used at different scales of investigation [76][77][78][79][80][81][82][83][84][85][86][87][88][89][90][91][92]. Moreover, the structural analysis of medical devices and biological tissues is strictly connected with the in-vivo behavior of their interaction [93,94].…”
Section: Discussionmentioning
confidence: 99%